Organizational Culture at University: A Sample of a State University, Faculty of Education - Bertan Akyol; Filiz Tanrısevdi; Yusuf Gidiş; Nahide Nur Dumlu; İlknur Durdu (Anı Publishing, 2020)
Culture is one of the most basic features that distinguishes an organization from others.  Organizations, like societies, have their own norms, beliefs and values. In culture formation, elements such as management style, manager style, members of the organization play an important role. Organizational culture is seen as a component of the characteristics of its members and can be shaped by their characteristics. This is also valid for universities as they are a form of organization. Sub-groups at universities can have a different culture from the university's own corporate culture and create their own structure. This may make the university an institution that synthesizes different subcultures. From a managerial point of view, it will be appropriate to examine how organizational culture is shaped in order to see the organizational culture and its effects in the loosely constructed universities. For this reason, this study aims to describe the organizational culture of a state university. In this context, the views of the lecturers about organizational culture were collected through qualitative research techniques by interviewing and analyzed by themes and categories. At the end of the study, the most commonly used cultural elements are determined as common values, communication, democracy, hierarchical structure and beliefs. The failure to create traditions due to ever-changing administrations has been identified as a factor that adversely affects the development of organizational culture. Organizing unifying activities in order to develop organizational culture, creating rituals and symbols, establishing a communication network for scientific cooperation and adapting to the new participants are among the proposals of the participants.